The Role of the Film and Television Series in representing the Tourism Destination: The Findings on Audience Decision Process and the Factor of Influences - LIU, CHUAN-PEI (2016)
This study examined the general power of films and series on building the country image on audiences, the impact on their perspective of the feature destination in the screen and their willingness of visiting the destination after viewing the films and series. Then the interview also ask the participants to compare the cultural differences of the screen-destination in order to know their motives of picking the films and series and found the pattern in the cultural aspect and the screen destination attribute. Furthermore, the interviewees also shared their past screen-tourism experience and their satisfaction level of it. Finally, the product CoO believes was tested on the participants in relation to the films/series influence. The results indicate that the role film and TV series is the influential mediating variable to deliver the country image to the audience. Although the audience will not accept all of the ideology inside the film, it enhances the country exposure without intent purpose of promoting the place and leaves the audience the impression. That will bring the audience the familiarity as a friendly hint whenever they see it in the future.